2015
DOI: 10.1159/000369511
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination and Other Antigen-Specific Immunomodulatory Strategies in Celiac Disease

Abstract: Background: Celiac disease (CD) results from an alteration in the oral tolerance to dietary gluten. The response to gluten is normally tightly regulated and involves the secretion of TGF-β and IL-10 from different subtypes of regulatory T cells (Tregs). Interestingly, in addition to proinflammatory cytokines, the inflamed CD mucosa also contains high levels of T cell-derived IL-10 compared with treated CD patients or normal donors. Furthermore, most studies describe an increase in the number of Foxp3+ Tregs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
4
0
2
Order By: Relevance
“…Hieraus leitet sich bereits die erste klinisch verwertbare Schlussfolgerung ab: Erstgradige Verwandte von Zöliakie-Betroffenen haben eine ca. 10 % Wahrscheinlichkeit, auch an einer Zöliakie zu leiden -unabhängig von einer vorhande- der ein Gemisch dreier immundominanter Glutensequenzen enthält, angewendet [9].…”
Section: (Fast) Alles Genetisch…unclassified
“…Hieraus leitet sich bereits die erste klinisch verwertbare Schlussfolgerung ab: Erstgradige Verwandte von Zöliakie-Betroffenen haben eine ca. 10 % Wahrscheinlichkeit, auch an einer Zöliakie zu leiden -unabhängig von einer vorhande- der ein Gemisch dreier immundominanter Glutensequenzen enthält, angewendet [9].…”
Section: (Fast) Alles Genetisch…unclassified
“…Starting with a small dose of antigen exposure and gradually increasing the dose to gradually build up a tolerance to the specific antigen and reduce the immune response. It is not possible to use natural antigens directly in the treatment of celiac disease, such as consuming foods containing gluten, as this could exacerbate the condition in those who already suffer from it [7].…”
Section: Administration Routes For Vaccinesmentioning
confidence: 99%
“…One idea is to still use oral administration to deliver gliadin to patients to build tolerance. To avoid exacerbation by direct intestinal exposure to the antigenic protein, gliadin was modified to be nontoxic [8] and delivered via genetically modified non-stereotypic, non-pathogenic bacteria [7,8].…”
Section: Administration Routes For Vaccinesmentioning
confidence: 99%
“…Over time and due to the global problems of CD, researchers have developed various ways to avoid the adverse effects of gliadin, such as: genetically modified wheat cultivars, transamidated gliadins that revert the inflammatory phenotype by an anti-inflammatory in the gliadin-inducible immune response and a desensitizing vaccine (NexVax2) that have three dominant gluten peptides and induces tolerogenic response in CD patients [30,31] . Also, researchers have demonstrated that anti-wheat gliadin IgY antibody produced in their study has proved to inhibit absorption of gliadin and gliadin-induced inflammatory process in Caco2 cell culture model of CD.…”
Section: Introductionmentioning
confidence: 99%